Additive manufacturing : design, methods, and processes - Killi, Steinar Westhrin (Pan Stanford Publishing, 2017)
"Additive manufacturing has matured from rapid prototyping through the now popular and "maker"--Oriented 3D printing, recently commercialized and marketed. The terms describing this technology have changed over time, from "rapid prototyping" to "rapid manufacturing" to "additive manufacturing," which reflects largely a focus on technology. This book discusses the uptake, use, and impact of the additive manufacturing and digital fabrication technology. It augments technical and business-oriented trends with those in product design and design studies. It includes a mix of disciplinary and transdisciplinary trends and is rich in case and design material. The chapters cover a range of design-centered views on additive manufacturing that are rarely addressed in the main conferences and publications, which are still mostly, and importantly, concerned with tools, technologies, and technical development. The chapters also reflect dialogues about transdisciplinarity and the inclusion of domains such as business and aesthetics, narrative, and technology critique. This is a great textbook for graduate students of design, engineering, computer science, marketing, and technology and also for those who are not students but are curious about and interested in what 3D printing really can be used for in the near future."--Provided by publisher.